2014
DOI: 10.1038/nbt.3002
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the epicardial lineage from human pluripotent stem cells

Abstract: The epicardium supports cardiomyocyte proliferation early in development and provides fibroblasts and vascular smooth muscle cells to the developing heart. The epicardium has been shown to play an important role during tissue remodeling after cardiac injury, making access to this cell lineage necessary for the study of regenerative medicine. Here we describe the generation of epicardial lineage cells from human pluripotent stem cells by stage-specific activation of the BMP and WNT signaling pathways. These cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
193
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(212 citation statements)
references
References 49 publications
9
193
1
Order By: Relevance
“…Taken together, Tbx18-positive cells give rise to vascular SMCs and fibroblasts through EMT in vitro. Witty et al reported that the basic fibroblast growth factor and transforming growth factor beta were important for differentiation of epicardial cells derived from human iPS cells into vascular SMCs and fibroblasts (23). Whether Tbx18-EGFP-positive cells need these growth factors is the future research direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, Tbx18-positive cells give rise to vascular SMCs and fibroblasts through EMT in vitro. Witty et al reported that the basic fibroblast growth factor and transforming growth factor beta were important for differentiation of epicardial cells derived from human iPS cells into vascular SMCs and fibroblasts (23). Whether Tbx18-EGFP-positive cells need these growth factors is the future research direction.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardium is localized on the outer surface of the heart and composes the heart together with the inner endocardium and the central myocardium. Epicardium contributes not only to proper embryonic development of the heart but also to cardiac repair during a disease (23). This indicates that progenitor cells of epicardium could be one of the cell sources for cell-based regenerative medicine in patients with heart diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of this strategy comes from the lab of Gordon Keller (McEwen Centre for Regenerative Medicine, Canada), who spoke about his aim to produce all the different cell types present in the adult heart via directed differentiation. Keller stressed the importance of replicating in vivo developmental processes to achieve this aim, and showed how the derivation of atrial and ventricle cardiomyocytes, pacemaker cells and epicardial cells can be simplified to controlling the expression of BMP and Wnt at specific time points from the mesoderm stage (Witty et al, 2014).…”
Section: Cell Differentiation and Disease Modelingmentioning
confidence: 99%
“…And more specifically proepicardial VSMCs are generated from hPSCs by precisely controlled administration of BMP2, 19 which crucially require activation of the BMP and Wnt signaling pathways to induce epithelial to mesenchymal transition for further specification toward the VSMC phenotype. 20 Meanwhile, neuroectoderm-derived VSMC generation requires FGF2 and activin inhibition, whereas paraxial mesoderm-derived VSMC generation requires initial BMP4 signaling with FGF2 and PI3K (phosphatidylinositol-4,5-bisphosphate 3-kinase) inhibition 21 ( Figure 1). Because iPSCs are derived from terminally differentiated cells, it is important to consider cell lineage commitment pathways during differentiation.…”
Section: Vsmc Origin and Differentiationmentioning
confidence: 99%